2015
DOI: 10.1037/a0038878
|View full text |Cite
|
Sign up to set email alerts
|

Examining patient characteristics as predictors of patient beliefs about treatment credibility and expectancies for treatment outcome.

Abstract: Although it is widely documented that a patient’s expectations for treatment outcome and credibility beliefs about treatment are consistent correlates of outcomes across settings and treatment modalities, few data exist regarding predictors of these expectations and beliefs. The current study aimed to test specific patient characteristics, such as demographic variables (e.g., age, sex, race) and clinical variables (e.g., diagnosis, level of depression, anxiety), as predictors of treatment expectancy, and credi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 40 publications
1
19
1
3
Order By: Relevance
“…Finally, regarding the predictive validity of CEQ and symptomatic decrease in session 3, our results suggest that outcome expectation, specifically, has an effect in decreasing symptoms. These results are consistent with those of other validations (Cohen et al, 2015;Devilly & Borkovec, 2000;Smeets et al, 2008), which evidence that outcome expectation predict the decrease of the depressive and anxiety symptoms, treatment satisfaction and the improvement of well-being.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Finally, regarding the predictive validity of CEQ and symptomatic decrease in session 3, our results suggest that outcome expectation, specifically, has an effect in decreasing symptoms. These results are consistent with those of other validations (Cohen et al, 2015;Devilly & Borkovec, 2000;Smeets et al, 2008), which evidence that outcome expectation predict the decrease of the depressive and anxiety symptoms, treatment satisfaction and the improvement of well-being.…”
Section: Discussionsupporting
confidence: 91%
“…The credibility/expectancy questionnaire (CEQ) (Devilly & Borkovec, 2000) is one of the mostly used measures to assess the client's credibility and expectancy, which has shown results not only in reducing depressive, anxiety and general symptoms, but also in the increase of the therapeutic alliance in the psychotherapy (cf. Cohen, Beard, & Björgvinsson, 2015;Greenberg, Constantino, & Bruce, 2006;Newman & Fisher, 2010;Sochting, Tsai, & Ogrodniczuk, 2016;Stinson, Perez, Ohrt, Von Schell, & Bruening, 2018;Thompson-Hollands, Bentley, Gallagher, Boswell, & Barlow, 2014;Tompkins, Swift, Rousmaniere, & Whipple, 2017). It is a self-report questionnaire composed by 6 items clustered in two subscales: i) credibility; and ii) outcome expectation (Devilly & Borkovec, 2000).…”
mentioning
confidence: 99%
“…Positive expectations for treatment depend, at least in part, on agreement between the patient and the clinician on the goals of treatment as well as the specific components of the therapy. 30 Thus, open discussion about the goal (tic reduction) and techniques of CBIT (e.g., awareness training and competing response training) between the therapist and the patient is warranted.…”
Section: Resultsmentioning
confidence: 99%
“…This relationship appears to exist for various anxiety disorders (e.g. [8,10,16]). However the question arises as to which specific mechanisms cause the expectations of a patient to affect the change process [11].…”
Section: Methods Study Objectives and Designmentioning
confidence: 97%
“…Although CBT is recognized as an empirically welldocumented treatment, the exact mechanisms that cause a change have not been explored so far [7]. Studies investigating the effectiveness of CBT in psychotherapy have shown that the positive treatment expectations of a patient play a central role and are directly related to the therapy result [8][9][10]. However, again little is known about the specific mechanisms responsible…”
Section: Introductionmentioning
confidence: 99%